(untitled) (Nexo Revista Científica, 2023)
Morphometric, morphographic, and structural analysis should be combined since orographic features directly reflect the tectonic structure of the territory. In the study, the authors supplemented these types of analysis with the photograph analysis method which allowed them to study the relief of the coastline better. The results of the analysis showed that the close contact of the Caucasus mountain system with the Black Sea and the high dissection of the relief predetermined the intensity of economic activity on the coast. This makes it necessary to constantly monitor the activity of exogenous and endogenous processes, in particular, seismic activity, to prevent their adverse manifestations.